Male survivors of wartime sexual violence: perspectives from northern Uganda - Schulz, Philipp (University of California Press, 2021)
Introduction -- Conflict-related sexual violence against men : a global perspective -- Tek-gungu : wartime sexual violence in Northern Uganda -- 'I used to be a strong man, but now I am not' : gendered vulnerabilities and harms -- Exercising agency : survivors' support groups -- Justice, recognition, and reparations -- Towards a survivor-centric approach.